Subspace distribution clustering hidden Markov model. - Bocchieri, E.
Most contemporary laboratory recognizers require too much memory to run, and are too slow for mass applications. One major cause of the problem is the large parameter space of their acoustic models. In this paper, we propose a new acoustic modeling methodology which we call subspace distribution clustering hidden Markov modeling (SDCHMM) with the aim of achieving much more compact acoustic models. The theory of SDCHMM is based on tying the parameters of a new unit, namely the subspace distribution, of continuous density hidden Markov models (CDHMMs). SDCHMMs can be converted from CDHMMs by projecting the distributions of the CDHMMs onto orthogonal subspaces, and then tying similar subspace distributions over all states and all acoustic models in each subspace, by exploiting the combinatorial effect of subspace distribution encoding, all original full-space distributions can be represented by combinations of a small number of subspace distribution prototypes. Consequently, there is a great reduction in the number of model parameters, and thus substantial savings in memory and computation. This renders SDCHMM very attractive in the practical implementation of acoustic models. Evaluation on the Airline Travel Information System (ATIS) task shows that in comparison to its parent CDHMM system, a converted SDCHMM system achieves seven- to 18-fold reduction in memory requirement for acoustic models, and runs 30%-60% faster without any loss of recognition accuracy
Keywords: ATIS task; Airline Travel Information System; CDHMM; SDCHMM; Acoustic models; Combinatorial effect; Continuous density hidden Markov models; Full-space distributions; Memory requirement; Orthogonal subspaces; Subspace distribution clustering hidden Markov model; Subspace distribution encoding